Next-generation sequencing reveals clinical features and prognosis of gene mutations in Chinese children with T-cell acute lymphoblastic leukaemia - Zhang, Senlin; Chu, Xinran; Li, Zhiheng; Ji, Qi; Meng, Na; Gao, Wei; Zhang, Xiao; Hu, Yixin; Gao, Li; Li, Bohan; Chen, Ping; Wan, Huihui; et al. (Frontiers in Oncology, 2025)
Background and objectiveThe 5-year overall survival (OS) for paediatric T-cell acute lymphoblastic leukaemia (T-ALL) exceeds 80% under the current treatment strategies; however, some patients suffer from treatment failure. Next-generation sequencing (NGS) identified recurrent mutated genes in T-ALL that might affect diagnosis, classification, prognostic stratification, and treatment response. This study aimed to characterise the clinical features and prognosis of gene mutations in paediatric patients with T-ALL.MethodsWe enrolled 144 paediatric patients with T-ALL at our centre. Chi-square or Fisher’s exact tests were used for categorical variables, and Kaplan–Meier and log-rank tests analysed the survival rates of these patients.ResultsThe most common mutations were in NOTCH1 (58.3%), FBXW7 (19.4%), and PTEN (17.4%). Of 1262 gene mutations detected, 50 had a mutation frequency of >1%. Common mutations were not correlated with 5-year OS. Patients with higher NOTCH1 mutation loads had a lower proportion of D15 minimal residual disease ≥0.01% and better survival than those with a lower load.ConclusionThis study reported the gene mutation spectrum of Chinese paediatric T-ALL, highlighting the role of NGS in molecular classification, risk stratification, and prognosis. Additionally, we emphasised the role of the variant allele frequency of NOTCH1 mutations in the treatment response and prognosis of childhood T-ALL.